Does Lateral Extraarticular Tenodesis Lead to Poor Patellofemoral Outcome in ACL Revision on Professional Soccer Players? A Minimum 3-Year, Clinical Radiographic Retrospective Study - Alessio-Mazzola, Mattia; Russo, Antonio; Ahmadi, Sean; Placella, Giacomo; Felli, Lamberto; Salini, Vincenzo (The Journal of Knee Surgery, 2025)
Lateral extra-articular tenodesis (LET) is indicated to decrease the pivot shift and to restore rotational control in anterior cruciate ligament (ACL) surgery. However, there are still concerns regarding the patellofemoral joint, as with increased tension on the iliotibial band, there is a hypothetical increase of lateralizing forces on the lateral patellar surface. To compare clinical and radiographic patellofemoral outcomes of professional soccer players who underwent LET and ACL revision with a control group of professional soccer players who underwent primary ACL reconstruction. Retrospective comparative study. Inclusion criteria were professional or elite soccer players with failed ACL reconstruction who underwent ACL revision and LET for anterior laxity >5 mm and a pivot-shift test >2. Exclusion criteria were a two-stage procedure, injuries to the contralateral knee, multi-ligament injuries, and patients with less than 3 years of follow-up. The control group was selected as standard ACL reconstruction with autograft in elite or professional soccer players. All included patients were assessed with a Tegner Lysholm, IKDC, and Kujala score. Patients recalled for radiographic patellofemoral assessment with bilateral skyline Merchant view which was compared with the contralateral unaffected knee. Sixty-four consecutive patients (30 in the study group and 34 in the control group) treated from 2015 to 2018 have been included in the study. All patients had a minimum 3-year follow-up, and the mean follow-up was 4.9 ± 2.8 (range: 3–7) years. Overall, patients demonstrated significant improvement in measured outcome measures from baseline to final follow-up. There were no significant differences between groups in Kujala, Tegner and Lysholm, and IKDC scores (p > 0.05). In the study group, no significant differences in lateral patellar tilt (p > 0.05) between treated and unaffected knees were found. LET represents a reliable solution to increase anteroposterior and rotational stability in revision ACL reconstruction with severe pivot shift. Clinical and radiographical results showed favorable patellofemoral outcomes, with clinical scores comparable to primary surgery and no significant patellar lateralization and degenerative changes.
Keywords: anterior cruciate ligament; revision; patellofemoral joint; lateral extraarticular tenodesis; Arnold–Coker; arthroscopy; knee